Efektivitas Pembelajaran Kimia Berbasis Proyek Terhadap Pemahaman Konsep Dan Ketrampilan Berpikir Kreatif Peserta Didik Smk - Halimatusa’adiah (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Project-Based Learning (PjBL) is highly relevant learning with a 21st century paradigm and competency framework formulated in the Partnership for 21st Century Skills, where 21st century student outcomes include learning and innovation skills that include creativity and innovation skills, thinking critical, and problem solving skills. , communication and collaboration skills (Partnership for 21st Century Skills, 2008). Based on observations of student learning at SMKN 6 Mataram, it shows that student learning outcomes are low (60% of students have not yet completed studying chemistry), and based on a search for alumni in October 2021, the alumni unemployment rate reaches 59.72%, the Project-based learning model (PjBL) is one way to do this. to resolve the issue. The PjBL learning model has a positive influence in improving problem solving, critical thinking, and creativity (Selçuk et al., 2013). This is supported by Miftahurrohmah et al 2021 who said that project-based learning using Zoom Meetings can have a positive influence on creative thinking skills and mastery of concepts. Therefore, it is necessary to train on “The Effectiveness of Project-Based Chemistry Learning on Concept Understanding and Creative Thinking Skills for Vocational Students. The training was held at SMKN 6 Mataram in April 2022. The population in this study were all X grade students of SMKN 6 Mataram in the 2021/2022 academic year. The sampling technique in this training uses the "purposive sampling" technique. The sample to be taken is class X DPIB which uses a project-based learning model. This sampling is based on the material to be tested, namely acid and base. There are two variables in this training, namely the independent variable and the dependent variable. The independent variable is a project-based learning model, where the project used is the identification of acids and bases on several building materials and materials that are often used in everyday life, while the dependent variable is mastery of concepts with six indicators, namely remembering, understanding, and understanding. apply (apply), analyze (analyze), evaluate (evaluate), create (create). and creative thinking skills with indicators of Fluency, flexibility, originality and elaboration. The type of data used in this training is quantitative data in the form of a Chemistry concept mastery test and a Creative Thinking Test. The effectiveness of the Project-based learning model for students of SMKN 6 Mataram on acid-base material can be determined by taking into account the pretest and posttest scores obtained by students. Based on the data obtained, it shows that project-based learning is effective in increasing students' understanding of concepts with a learning mastery percentage of 78%, and high effectiveness in improving students' creative thinking skills with an N gain of 81.79%.